Basic and clinical science course 1992-1993. Section 3, Optics, refraction, and contact lenses (American Academy of Ophthalmology, 1992)
The textbook focuses on basic and clinical science, ophthalmology, optics, refraction and contact lenses. Intended for professional public and for university students.
Keywords: refrakce oka; optika a fotonika; věda a výzkum; klinické lékařství; Clinical Medicine; věda; kontaktní čočky; Science; Ophthalmology; oftalmologie; Contact Lenses; Optics and Photonics; Refraction, Ocular